2019
DOI: 10.13075/mp.5893.00750
|View full text |Cite
|
Sign up to set email alerts
|

Job-related emotions and job burnout among civil servants: examining the shape of the relationship in cross-sectional and longitudinal models

Abstract: StreszczenieWstęp: Związek pozytywności, czyli proporcji między pozytywnymi a negatywnymi emocjami, z wypaleniem zawodowym może przybierać kształt krzywoliniowy. Ponadto z perspektywy teoretycznej jest to relacja przyczynowo-skutkowa, w której pozytywność jest proksymalnym, a wypalenie -dystalnym wymiarem dobrostanu zawodowego. Dotychczasowe badania były jednak prowadzone najczęściej w planie poprzecznym i testowały relacje prostoliniowe. Celem pracy było zbadanie kształtu relacji między pozytywnością a wypale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Following a comparison of the original and resultant versions, the final questionnaire was established, which was approved as an official Polish translation by the co-author of the BAT (Wilmar Schaufeli). The pilot study was conducted in a group of white-collar workers, resulting in satisfactory psychometric characteristics [41].…”
Section: The Bat-pl Translationmentioning
confidence: 99%
“…Following a comparison of the original and resultant versions, the final questionnaire was established, which was approved as an official Polish translation by the co-author of the BAT (Wilmar Schaufeli). The pilot study was conducted in a group of white-collar workers, resulting in satisfactory psychometric characteristics [41].…”
Section: The Bat-pl Translationmentioning
confidence: 99%
“…Some studies have linked disengagement at work with job burnout (Bakker and de Vries, 2020; Basinska and Gruszczynska, 2019; Harris, 2016). Cole and colleagues undertook a meta-analysis in 2011 and found that from the 37 studies reported, and there was a high degree of correlation between job disengagement and job burnout (Cole et al , 2011).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Disengaged employees lack enthusiasm and do not expend extra effort in the workplace, are unsupportive of working in teams and can consequently negatively influence morale and, therefore, organisational performance (Kahn, 1990, p. 693). Some studies have linked disengagement at work with job burnout (Bakker & de Vries, 2020;Basinska & Gruszczynska, 2019;Harris, 2016). Cole and colleagues undertook a metaanalysis in 2011 and found that from the 37 studies reported, there was a high degree of correlation between job disengagement and job burnout (Cole et al, 2011).…”
Section: Background and Literature Reviewmentioning
confidence: 99%